Epistemic Game on Aplication of Newton’s Laws - Puspitasari, M. Dewi Manikta (Program Studi Tadris IPA, Fakultas Tarbiyah (IAIN) Kediri, Indonesia, 2023)
Epistemic games are a problem-solving strategy used by students in the process of finding solutions to a given problem. This study aims to determine the epistemic game that is owned by students in solving Newton's law application problems. The method used is a qualitative method in which student problem-solving strategies are identified in six games. The research subjects were students taking physics and biology courses. Data collection uses interviews and concept understanding tests about the application of Newton's law. The results showed that students used different games between each other to solve Newton's law application problems. The epistemic games that students have include mapping meaning to mathematics, physical mechanism, pictorial analysis, and transliteration to mathematics. Students use different games with each other to solve Newton's law application problems. The process by which students determine the solution to the problem-solving application of Newton's law is influenced by their' understanding of the material. This research is limited in the form of an epistemic game analysis of the application of Newton's law, so that further research can be carried out on other material concepts.